2009
DOI: 10.1002/smi.1276
|View full text |Cite
|
Sign up to set email alerts
|

Burnout, coping and job satisfaction in service staff treating opioid addicts—from Athens to Zurich

Abstract: The Treatment‐systems Research on European Addiction Treatment study (TREAT‐project) is a longitudinal multicenter study on predominantly opioid‐dependent patients and their health‐care system in six European cities. As part of the examination of the drug services, this study evaluates level of burnout, coping strategies, perceived self‐efficacy and job satisfaction among health‐care workers treating opioid addicts. Employees were recruited from organizations in Athens, London, Padua, Stockholm, Zurich and Ess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
20
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 32 publications
3
20
1
Order By: Relevance
“…This finding is consistent with some occupational research; for example, Volker et al. () found that “passive” coping strategies, such as denial and withdrawal, were associated with “high emotional exhaustion” status among service staff treating opioid‐dependent patients in six European cities. In a study of health care professionals who worked in pediatric trauma, McGarry et al.…”
Section: Discussionsupporting
confidence: 90%
“…This finding is consistent with some occupational research; for example, Volker et al. () found that “passive” coping strategies, such as denial and withdrawal, were associated with “high emotional exhaustion” status among service staff treating opioid‐dependent patients in six European cities. In a study of health care professionals who worked in pediatric trauma, McGarry et al.…”
Section: Discussionsupporting
confidence: 90%
“…It was considered as a psychological syndrome specific to professionals performing human services or support tasks for other people (Maroco and Campos, 2012). Burnout is associated with negative organizational outcomes such as reduced job performance, absenteeism, turnover intention, lower career satisfaction, and reduced quality of service (Hultell and Gustavsson, 2010;Volker et al, 2010;Adekola, 2012). Burnout arises when there is significant disharmony between the nature of a person's job and the nature of the person doing the job.…”
Section: Introductionmentioning
confidence: 99%
“…The sources of stress in a medical practice are similar to what is found in many other occupations. For example, work load, team climate, procedural justice, perceived psychological distress, long sick leaves (Virtanen et al, 2008), seniority (Tinti et al,2009), economical problems (Fothergill, Edwards, & Burnard, 2004), work and work‐related activity (Cyr‐Taro et al, 2008; Kankaanranta et al, 2007; Volker et al, 2010), perception of unrealistic expectations (Falkum & Vaglum, 2005), communication skills (Geller et al, 2008; Smith et al, 2007), malpractice litigation (Annas, 2008; Papadopoulos, 2007), ethical dilemmas and lack of resources (Forde & Aasland, 2008) can all be sources of stress. Therefore, the OSI‐2 scales that have been used for other occupations can also be used to measure the sources of stress in the medical field (Siu, Lu, & Cooper, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…These factors, when combined with other problems such as limited resources and excessive legal regulation, may place doctors in difficult ethical dilemmas that can cause them much distress (Forde & Aasland, 2008). In fact, heavy work load (Tinti et al, 2009; Virtanen et al, 2008), poor job satisfaction (Cyr‐Taro, Kotwall, Menon, Hamann, & Nakayama, 2008; Kankaanranta et al, 2007; Volker et al, 2010), perception of unrealistic expectations from patients and their families, communication with colleagues (Falkum & Vaglum, 2005; McIntosh & Macario, 2008; Smith, Waldman, Hood, & Fottler, 2007), poor lifestyle (Hebbard & Wirtzfeld, 2009), limited resources (Forde & Aasland, 2008), interaction with patients (Geller, Bernhardt, Carrese, Rushton, & Kolodner, 2008; Mjaaland & Finset, 2009), and the threat and reality of medical malpractice litigation (Papadopoulos, 2007) can all be causes of job insecurity and resulting occupational stress in a medical practice. High levels of occupational stress may result in a medical practitioner's negative perception of job satisfaction and a more negative attitude about health care as a profession (Richardsen & Burke, 1991).…”
mentioning
confidence: 99%